The motivational approach of religion: the significance of religious orientation on customer behaviour - Abu-Alhaija, Ahmad Saif-Alddin; Raja Yusof, Raja Nerina; Hashim, Haslinda; Jaharuddin, Nor Siah (IJECM, 2017)
Most marketing studies used religious affiliation, religious commitment, and religiosity in measuring the influence of religion on customers' attitudes and behaviors. This study sheds light on the religious orientation as another religious factor that researchers should examine its influence to provide further understanding in the existing research models on customers' behaviors. The present study concludes that the religious orientation construct and its scale (ROS) should be used independently from other religious factors, such as, religious affiliation and religious commitment (religiosity).